2014
DOI: 10.1002/pd.4318
|View full text |Cite
|
Sign up to set email alerts
|

Reference charts for fetal biometric parameters in twin pregnancies according to chorionicity

Abstract: Reference curves of biometric parameters in twin pregnancies were determined. Biometric parameters were statistically different between monochorionic and dichorionic pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 20 publications
4
25
2
Order By: Relevance
“…The EFW at 36 0/7 weeks of gestation was 2294 g, which was similar to that reported by Min et al [ 10 ] and Gabbay-Benziv et al [ 14 ], but lighter than that reported by Shivkumar et al [ 13 ], Araujo Junior et al [ 12 ], and Liao et al [ 11 ] (Table 3 ). This difference may be mainly due to differences in the study population’s race.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The EFW at 36 0/7 weeks of gestation was 2294 g, which was similar to that reported by Min et al [ 10 ] and Gabbay-Benziv et al [ 14 ], but lighter than that reported by Shivkumar et al [ 13 ], Araujo Junior et al [ 12 ], and Liao et al [ 11 ] (Table 3 ). This difference may be mainly due to differences in the study population’s race.…”
Section: Discussionsupporting
confidence: 86%
“…Several reports have described a relationship between chorionicity and EFW for twins [ 10 , 12 14 ] (Table 3 ). Min et al [ 10 ] reported that MC twins were slightly lighter than DC twins; however, the difference was slight, and the proportions of races differed between the DC and MC populations.…”
Section: Discussionmentioning
confidence: 99%
“…Their study demonstrated a lower EFW among twins compared with singletons, especially in the third trimester, with a larger difference compared with monochorionic twins than with dichorionic twins. Araujo et al constructed chorionicity‐specific references from a Brazilian population. Unlike other studies, they used a cross‐sectional methodology; however, despite the use of an ultranormal cohort (excluding all maternal chronic disease including diabetes and hypertension, as well as twin discordance), a comparison of references yielded similar EFWs for dichorionic twins relative to our results, up to 32 gestational weeks (±30 g).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have recommended the creation of growth curves specific to twins or the use of some already existent curves for twin infants. [43][44][45][46] Among the unfavorable outcomes are fetal death and neonatal death. The fetal death rate is higher among twin pregnancies than in singleton pregnancies.…”
Section: Perinatal Outcomes In Twin Pregnancymentioning
confidence: 99%